«BEWARE OF FALSE PROPHETS WHO COME TO YOU IN SHEEP'S CLOTHING» - Elena Pavlovna Telmenko (Вестник Северо-Кавказского федерального университета)
The article, based on an the analysis of the letter by an anonymous church author, identifies the key issues of the 1495-1496's controversy that arouse among the Italian clergy about the Florentine prophet and reformer Girolamo Savonarola.